Arbitrase Online di Masa Pandemi:: Penguatan Peran Basyarnas dalam Menyelesaikan Sengketa Ekonomi Syariah Lintas Batas Negara - Heriyanto, Dodik; Diffaul Barraq Suwatono, Rahadian; Syahputra Lubis, Akhiruddin (Zaaken: Journal of Civil and Business Law, 2023)
In this pandemic situation, the need for online arbitration services is very urgent, especially for the business community. As a country with a majority of the Muslim population, Indonesia has established Basyarnas as an alternative dispute resolution institution based on sharia law. In the era of globalization, business disputes that occur today are not on disputes between citizens or legal entities originating from Indonesia only, but also, include disputes that have a cross-border nature, either because of the differences in the domicile of the parties or because of the choice of foreign law clause. This research will study the role and readiness of Basyarnas in resolving cross-border disputes. Besides that, the implications of the arbitration award issued by Basyarnas will also be studied from disputes that contain foreign elements. These two problems will be studied using a normative legal research method with a statutory and conceptual approach. Through this research, it can be concluded that: first, Basyarnas as a sharia arbitral award in Indonesia should have competence and ability to handle sharia disputes that are cross-border; and second, because of the existence of foreign elements in sharia relationship from both parties, it is necessary to recognize sharia arbitral award in the country where the assets are located.